Mechanistic Modeling of Water Vapour Condensation in Presence of Noncondensable Gases - Karkoszka, Krzysztof (KTH, Reaktorteknologi, 2007)
This thesis concerns the analytical and numerical analysis of the water vapour condensation from the multicomponent mixture of condensable and noncondensable gases in the area of the nuclear reactor thermal-hydraulic safety. Following an extensive literature review in this field three aspects of the condensation phenomenon have been taken into consideration: a surface condensation, a liquid condensate interaction with gaseous mixtures and a spontaneous condensation in supersaturated mixtures. In all these cases condensation heat and mass transfer rates are significantly dependent on the local mixture intensive parameters like for example the noncondensable species concentration. In order to analyze the multicomponent mixture distribution in the above-mentioned conditions, appropriate simplified physical and mathematical models have been formulated. Two mixture compositions have been taken into account: a binary mixture of water vapour with heavy noncondensable gas and a ternary mixture with two noncondensable gases with different molecular weights. For the binary mixture a special attention has been focused on the heavy gas accumulation in the near-interface region and the influence of liquid film instabilities on the interface heat and mass transfer phenomena. For the ternary mixture of gases a special attention has been paid to the influence of the light gas and induced buoyancy forces on the condensation heat and mass transfer processes. Both analytical and numerical methods have been used in order to find solutions to these problems. The analytical part has been performed applying the boundary layer approximation and the similarity method to the system of film and mixture conservation equations. The numerical analysis has been performed with the in-house developed code and commercial CFD software. Performing analytical and CFD calculations it has been found that most important processes which govern the multicomponent gas distribution and condensation heat transfer degradation are directly related to the interaction between interface mass balances and buoyancy forces. It has been observed that if the influence of the liquid film instabilities is taken into consideration the heat transfer enhancement due to the presence of different types of waves is directly related to the internal film hydrodynamics and shows up in the mixture-side heat transfer coefficient. The model developed for the dispersed phase growth shows that degradation of the condensation heat transfer rate, which is a consequence of degradation of the convective mass flux, should be taken into account for highly supersaturated gaseous mixtures and can be captured by combination with the mechanistic CFD surface condensation model. Keywords: condensation, noncondensable gases, CFD simulation, boundary-layer approximation, binary and ternary mixtures === QC 20100623